Desentralisasi Setengah Hati: Hambatan Struktural Dalam Optimalisasi Kewenangan Pemerintah Desa - Moh. Khalilullah A. Razaq; Abd. Manab; Musfianawati Musfianawati; Nanang Tri Budiman (Prodi Ilmu Hukum Fakultas Hukum Universitas Islam Jember, 2026)
This study aims to analyze the structural barriers that hinder the optimization of village government authority within the framework of decentralization as stipulated in Law No. 6 of 2014 on Villages, specifically Articles 18–20. Normatively, villages are granted the authority to regulate and manage their own interests; however, in practice, this has not yet been fully realized. This study employs a normative legal research method using the statutory approach. Additionally, it utilizes the analytical approach and the historical approach. The research results indicate several structural obstacles to the optimization of authority, namely: (1) low understanding among village officials regarding the concept of village authority; (2) an inability to formulate Village Regulations (Perdes) based on community potential and needs; (3) weak coordination between levels of government; (4) strong intervention by local governments in village affairs; and (5) a tendency toward re-centralization.This study contributes to a critical understanding of decentralization practices at the village level and recommends strengthening institutional capacity and reformulating the relationship between local governments and villages. Additionally, legal and technical assistance is needed in drafting Village Regulations so that villages can exercise their authority independently and accountably.